High-strength glueing maintenance treatment method for high-voltage insulator

CN122977786APending Publication Date: 2026-10-27JINGYUAN ELECTRIC (JIANGXI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611153182.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]针对现有技术的不足,本发明提供了一种高压绝缘子高强度胶装养护处理方法,解决了现有高压绝缘子胶装工艺在追求快速脱模早强时,难以兼顾浆体施工流动性,且极易因常规高温养护或高碱添加剂诱发内部微裂纹与长期碱硅酸反应破坏的问题

Benefits of technology

1、本发明通过甲酸钙分段加入工艺,将第一部分甲酸钙随干粉混入,将第二部分甲酸钙配制成水溶液并在湿拌后期加入,使早强组分的加入时机与浆体分散、注浆和初期硬化过程相匹配。与一次性加入全部甲酸钙的方式相比,该工艺有利于兼顾注浆阶段的流动度保持、振动排气和后续早期强度发展。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application relates to the technical field of high-voltage insulator manufacturing processes, and discloses a high-strength glue-fixing curing treatment method for a high-voltage insulator, which comprises the following steps: dry mixing a base material composed of silicate cement, slag micro-powder and superfine limestone powder, quartz sand and a first part of calcium formate; wet mixing with main mixing water added with a pre-stable low-sodium nano-silicon-PCE mother liquor B and a defoaming agent; injecting a second part of calcium formate aqueous solution in the late wet mixing period to prepare a low-water-binder-ratio slurry; and sequentially carrying out room temperature static standing, 53-57 DEG C constant temperature wet heat curing and natural cooling after grouting. The calcium formate is added in sections and delayed, and moderate temperature step curing is adopted, so that the strength required for early conversion can be obtained under the premise of guaranteeing the construction fluidity of the slurry, and the adverse effects of higher temperature and wet heat curing and additional alkali metal ions on the volume stability and long-term durability of the glue-fixing layer are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-voltage insulator manufacturing technology, specifically to a high-strength adhesive bonding and maintenance method for high-voltage insulators. Background Technology

[0002] High-voltage line insulators are typically made of insulating porcelain parts and metal fittings bonded together with inorganic cementing materials. The grout needs to have good fluidity during the grouting stage to fill the bonding gaps and facilitate vibration for air removal; at the same time, it needs to quickly form early strength after grouting to meet the requirements of production line transfer and handling.

[0003] In existing insulator bonding processes, early strength is often improved by increasing the humidity and heat curing temperature or adding early-strength agents. However, high-temperature humidity and heat curing can easily lead to problems such as temperature gradients, volume deformation, and insufficient strength growth in the later stages; adding early-strength agents at once or in excessive amounts can also affect the fluidity of the grout over time and the construction operation window.

[0004] Furthermore, while low water-cement ratios and nano-silica materials can improve the density of adhesive materials, they can also increase the difficulty of dispersing the slurry. When nanomaterials are directly added to the cement system, uneven dispersion or agglomeration can easily occur, which in turn affects the fluidity of the fresh slurry and the macroscopic uniformity after hardening.

[0005] Therefore, this invention proposes a high-strength adhesive bonding maintenance method for high-voltage insulators to address the shortcomings of existing technologies. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides a high-strength adhesive bonding and curing treatment method for high-voltage insulators. This method solves the problems of existing high-voltage insulator adhesive bonding processes, which, while pursuing rapid demolding and early strength, struggle to maintain the fluidity of the adhesive during application and are prone to internal micro-cracks and long-term alkali-silica reaction damage induced by conventional high-temperature curing or high-alkali additives.

[0007] To address the above problems, the present invention provides the following technical solution: This invention provides a method for high-strength adhesive bonding maintenance of high-voltage insulators, which adopts the following technical solution.

[0008] A method for high-strength adhesive bonding maintenance of high-voltage insulators includes the following steps: A cementitious base containing silicate cement, slag powder, and ultrafine limestone powder is mixed with the first portion of calcium formate to form a uniform dry premixed powder. Quartz sand is then added, and dry mixing continues. Deionized water is measured as the main mixing water, and pre-stabilized low-sodium nano-silicon-PCE mother liquor B and a defoamer are added to it. After stirring and dispersing evenly, a main mixture is obtained. The main mixture is added to the dry premixed powder for wet mixing. After the main mixture contacts the powder and is stirred for a first preset time, a post-calcium source water prepared by dissolving the second portion of calcium formate in reserved deionized water is injected into the material being stirred, and stirring continues. In the second preset time, an insulator adhesive slurry is prepared; the insulator adhesive slurry is injected into the adhesive gap between the insulator porcelain and metal fittings, and the surface is vibrated to remove air and smoothed; the grouted insulator is moved into a curing box and left to stand for 90 minutes at a temperature of 22℃~25℃ and a relative humidity of not less than 95%; after the standing period, the temperature of the curing box is raised to 53℃~57℃ at a heating rate of 5℃ / h~8℃ / h, and then kept at this temperature for 10 hours~12 hours; after the temperature is kept constant, the temperature inside the curing box is allowed to cool naturally to no higher than 35℃, and the insulator is removed from the curing box.

[0009] By adopting the above technical solution, combining the segmented feeding process of calcium formate, the pre-stabilized low-sodium nano-silicon-PCE mother liquor B, and the stepped temperature curing system, it is beneficial to maintain the fluidity of the slurry during construction, improve the early strength of the adhesive, and reduce the adverse effects of high-temperature humid heat curing on the later strength retention and volume stability.

[0010] In the above method, the pre-stabilized low-sodium nano-silica-PCE mother liquor B is first mixed with the main mixing water to form the main mixture, and then contacted with the dry premixed powder. The polycarboxylate superplasticizer can disperse cement particles, mineral admixture particles, and nano-silica particles, thereby improving the initial fluidity of the slurry. The first part, calcium formate, enters the system with the dry premixed powder to provide initial early strength components; the second part, calcium formate, is added in the form of an aqueous solution in the later stage of wet mixing to further regulate the setting and early hardening process after the slurry has completed its initial dispersion. By dividing the calcium formate into two stages—initial addition and subsequent addition—the working time and early strength development of the slurry can be considered to a certain extent.

[0011] Post-grouting static curing and stepped temperature increase curing are used to coordinate with the setting and hardening process of the grout. The static curing stage allows the grout to complete its initial structural formation before heating; subsequently, the temperature is increased at a rate of 5℃ / h to 8℃ / h to 53℃ to 57℃ and maintained at a constant temperature, which is beneficial for promoting cement clinker hydration, the early strength effect of calcium formate, and subsequent reaction processes involving components such as slag powder and nano-silica. Compared with higher temperature humid heat curing, the low temperature humid heat curing regime is beneficial for reducing the adverse effects of temperature gradient and volume deformation on the adhesive layer and interface.

[0012] Preferably, based on the total mass of the cementitious base, the cementitious base consists of 83%–88% silicate cement, 9%–13% slag powder, and 3%–4% ultrafine limestone powder by mass percentage. Based on the total mass of the cementitious base, the addition amount of pre-stabilized low-sodium nano-silica-PCE mother liquor B is 3.3%–3.9%, the addition amount of the first part calcium formate is 0.15%–0.20%, the addition amount of the second part calcium formate is 0.37%–0.42%, the addition amount of defoamer is 0.03%–0.05%, and the mass ratio of quartz sand to cementitious base is 1.0:1–1.15:1. The first and second parts of calcium formate are calcium formate added separately from the pre-stabilized low-sodium nano-silica-PCE mother liquor B.

[0013] Preferably, the total water-to-binder ratio of the insulator adhesive slurry is 0.22–0.26; the total water content in the calculation of the total water-to-binder ratio includes the mass of the main mixing water, the mass of water contained in the pre-stabilized low-sodium nano-silica-PCE mother liquor B, and the mass of reserved deionized water; the mass of reserved deionized water accounts for 12%–20% of the total mass of the main mixing water and the reserved deionized water. The silicate cement is P.O52.5R type ordinary silicate cement; the slag powder is S95 grade granulated blast furnace slag powder; the median particle size D50 of the ultrafine limestone powder is 2μm–6μm; and the defoamer is a nonionic organosilicon defoamer.

[0014] By adopting the above technical solution, the total water-to-binder ratio is controlled at 0.22–0.26, and the water content in the pre-stabilized low-sodium nano-silicon-PCE mother liquor B is included in the total water volume. This helps control the free water content in the hardened adhesive, reducing bleeding, drying shrinkage, and porosity defects. The addition of a nonionic silicone defoamer helps reduce air bubbles introduced during stirring and pouring, thereby improving the macroscopic uniformity of the hardened adhesive layer.

[0015] Preferably, the final solid mass fraction of the pre-stabilized low-sodium nano-silica-PCE mother liquor B is 18.1% to 22.9%, and the solid mass ratio of nano-SiO2 to polycarboxylate superplasticizer in the pre-stabilized low-sodium nano-silica-PCE mother liquor B is 4:1 to 5:1. The low-sodium nano-silica sol is a nano-silica sol dispersion that has undergone sodium removal treatment, and its Na2O equivalent is not higher than 0.10%.

[0016] Preferably, the preparation method of the pre-stabilized low-sodium nano-silica-PCE mother liquor B includes the following steps: adding deionized water and ether polycarboxylate superplasticizer with a solid mass fraction of 40% to 50% from the factory into a reaction vessel, and stirring at a speed of 300 r / min to 500 r / min for 5 to 10 minutes at a temperature of 20°C to 25°C; while maintaining stirring, adding low-sodium nano-silica sol with a solid mass fraction of 20% to 30% at a uniform rate to the reaction vessel over a period of 15 to 25 minutes; after the addition is completed, increasing the speed to 1800 r / min to 2500 r / min and continuing to stir for 20 to 30 minutes; dissolving calcium formate in pre-weighed deionized water to form a clear liquid, and then adding the clear liquid at a uniform rate to the reaction vessel over a period of 5 to 10 minutes; after the addition is completed, adjusting the speed to 1000 r / min to 1500 r / min, and continuing to stir for 15 to 20 minutes before discharging the material.

[0017] Preferably, based on a total mass of 1000 parts of the pre-stabilized low-sodium nano-silicon-PCE mother liquor B, the raw materials used to prepare the pre-stabilized low-sodium nano-silicon-PCE mother liquor B include: 63.5 to 319 parts of deionized water for use as bottom water in the reactor; 68 to 87.5 parts of ether-based polycarboxylate superplasticizer with a solid mass fraction of 40% to 50%; 510 to 700 parts of low-sodium nano-silicon sol with a solid mass fraction of 20% to 30%; 11 to 19 parts of calcium formate; and 75 to 130 parts of deionized water for dissolving calcium formate. The amounts of each raw material are selected within the above range, and the total mass of the pre-stabilized low-sodium nano-silicon-PCE mother liquor B is 1000 parts, the final solid mass fraction is 18.1% to 22.9%, and the solid mass ratio of nano-SiO2 to polycarboxylate superplasticizer is 4:1 to 5:1; wherein, the mass ratio of calcium formate to deionized water used to dissolve calcium formate is 0.08:1 to 0.15:1.

[0018] By adopting the above technical solution, nano-silica and polycarboxylate superplasticizer are first pre-dispersed in the aqueous phase, and then a small amount of calcium formate is added to adjust the ionic environment. This helps reduce the agglomeration tendency of nano-silica when directly added to the cement system and improves the dispersion uniformity and fluidity retention of the fresh mortar over time. Using low-sodium nano-silica sol helps reduce the content of soluble sodium ions introduced into the system by the admixtures, thereby improving the long-term durability of the adhesive system.

[0019] Preferably, wet mixing is performed using a planetary cement mortar mixer; timing begins the instant the main mixture contacts the powder, with a first preset time of 90 seconds and a second preset time of 90 seconds. Vibration and exhaust time is 30 seconds; the curing chamber is a programmable temperature and humidity curing chamber; the temperature inside the curing chamber is allowed to cool naturally by cutting off the heating power.

[0020] By adopting the above technical solution, the wet mixing process is divided into an initial wet mixing stage of the main mixture and powder, and a continued wet mixing stage after the addition of calcium source water. This facilitates the initial wetting of the powder and dispersion of the slurry before the uniform mixing of the calcium source water. After curing, natural cooling is used, which helps to reduce the interfacial stress caused by the difference in cooling rate between the insulator ceramic parts, metal accessories, and adhesive layer, thereby improving the stability of the adhesive interface.

[0021] This invention provides a method for high-strength adhesive bonding maintenance of high-voltage insulators. It has the following beneficial effects: 1. This invention employs a staged calcium formate addition process. The first portion of calcium formate is mixed in with the dry powder, while the second portion is prepared as an aqueous solution and added during the later stages of wet mixing. This ensures that the timing of the early-strength component addition matches the slurry dispersion, grouting, and initial hardening processes. Compared to adding all calcium formate at once, this process is beneficial for maintaining fluidity during the grouting stage, vibration venting, and subsequent early strength development.

[0022] 2. This invention utilizes a pre-prepared pre-stabilized low-sodium nano-silica-PCE mother liquor B, which pre-disperses and compoundes the low-sodium nano-silica sol, polycarboxylate superplasticizer, and trace amounts of calcium formate in the aqueous phase. This reduces the agglomeration tendency of nano-silica when directly added to the gelling system and improves the initial dispersion state and fluidity retention of the freshly mixed slurry over time. Simultaneously, the low-sodium nano-silica sol reduces the soluble sodium ion content introduced by added components, which is beneficial for improving the long-term durability of the adhesive material.

[0023] 3. This invention employs a stepped curing system consisting of room temperature static curing, low-temperature humid heat curing at 53°C to 57°C, and natural cooling. This curing system promotes early hydration and strength development, and reduces the effects of temperature gradients, volumetric deformation, and interfacial stress caused by higher-temperature humid heat curing, thereby improving the load-bearing capacity of glued parts under alternating hot and cold conditions.

[0024] 4. This invention comprehensively calculates the water content of the main mixing water, the reserved deionized water, and the mother liquor B, controlling the total water-to-binder ratio of the slurry within the range of 0.22 to 0.26. In conjunction with the use of a non-ionic silicone defoamer, it helps to reduce bleeding, drying shrinkage, and macroscopic pore defects, thereby improving the macroscopic uniformity of the hardened adhesive layer. Detailed Implementation

[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0026] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Unless otherwise stated, all chemical reagents are commercially available analytical grade or higher products; cement, slag powder, quartz sand, limestone powder and admixtures are all commercially available industrial products and meet the corresponding product standards.

[0027] The silicate cement used is ordinary silicate cement of type P.O52.5R that meets the corresponding strength grade requirements in GB175. The slag powder used is granulated blast furnace slag powder that meets the S95 grade requirements in GB / T18046. The ultrafine limestone powder has a calcium carbonate mass fraction of not less than 95% and a median particle size D50 of 2-6 μm. The quartz sand used is graded washed quartz sand with a fineness modulus of 1.5-2.5 and a mud content of less than 1.0%.

[0028] The calcium formate used is industrial-grade calcium formate (CAS No.: 544-17-2) with a mass fraction of not less than 98% and a moisture mass fraction of less than 0.5%. The nonionic silicone defoamer is a polydimethylsiloxane-based defoamer, preferably polydimethylsiloxane with CAS No. 9006-65-9 and a kinematic viscosity of 500-1000 mmHg. 2 / s.

[0029] Low-sodium nano-silica sol is a colloidal dispersion of amorphous silica (CAS No.: 7631-86-9) in an aqueous phase. Its SiO2 solid mass fraction is 20%-30%, and the nanoparticle size distribution is 10-20 nm. The specific surface area, measured according to the supplier's test report or the BET method, is 150-250 m². 2 / g and the Na2O equivalent after desodiumization treatment is not higher than 0.10%.

[0030] Ether-based polycarboxylate superplasticizers are comb-shaped polycarboxylate copolymers obtained by polymerization of isopentenyl alcohol polyoxyethylene ether and acrylic acid as the main monomers. The main polymer chain is composed of carbon-carbon single bonds, and the side chains are flexible segments with polyoxyethylene groups. The polymer molecular chain has carboxyl functional groups. Its weight-average molecular weight (Mw) is 30,000-50,000, the polydispersity index (PDI) is 1.5-2.5, and the solid mass fraction at the factory is 40%-50%.

[0031] Preparation Example 1: This preparation example provides a method for preparing pre-steady-state low-sodium nano-silicon-PCE mother liquor B, including the following steps: (1) Measure 149g of deionized water and 85g of ether polycarboxylate superplasticizer with a solid mass fraction of 40% and add them to a reactor equipped with a disperser. Stir at 400r / min for 8 minutes at 22°C.

[0032] (2) While maintaining a stirring speed of 400 r / min, 680 g of low sodium nano silica sol with a solid mass fraction of 20% was added dropwise into the reactor over 15 minutes. After the addition was completed, the speed of the disperser was increased to 1800 r / min and stirring was continued for 25 minutes.

[0033] (3) Dissolve 11g of calcium formate in 75g of pre-weighed deionized water to form a clear liquid. Then, drop the clear liquid into the reactor at a uniform rate within 5 minutes. After the drop is completed, adjust the speed of the disperser to 1200r / min and continue stirring for 15 minutes before discharging.

[0034] (4) After sampling and testing, the final solid mass fraction of the prepared mother liquor B was 18.1%, of which the solid mass ratio of nano-SiO2 to polycarboxylate superplasticizer was 4:1; after the mother liquor B was left to stand for 24 hours at 20℃-25℃, there was no visible gelation, layering and hard precipitation.

[0035] Preparation Example 2: This preparation example provides a method for preparing pre-steady-state low-sodium nano-silicon-PCE mother liquor B, including the following steps: (1) Measure 319g of deionized water and 68g of ether polycarboxylate superplasticizer with a solid mass fraction of 50% and add them to a reactor equipped with a disperser. Stir at 500r / min for 5 minutes at 25°C.

[0036] (2) While maintaining a stirring speed of 500 r / min, 510 g of low sodium nano silica sol with a solid mass fraction of 30% was added dropwise into the reactor over 20 minutes. After the addition was completed, the speed of the disperser was increased to 2000 r / min and stirring was continued for 20 minutes.

[0037] (3) Dissolve 13g of calcium formate in 90g of pre-weighed deionized water to form a clear liquid. Then, drop the clear liquid into the reactor at a uniform rate within 8 minutes. After the drop is completed, adjust the speed of the disperser to 1500r / min and continue stirring for 20 minutes before discharging.

[0038] (4) After sampling and testing, the final solid mass fraction of the prepared mother liquor B was 20.0%, of which the solid mass ratio of nano-SiO2 to polycarboxylate superplasticizer was 4.5:1; after the mother liquor B was left to stand for 24 hours at 20℃-25℃, there was no visible gelation, layering and hard precipitation.

[0039] Preparation Example 3: This preparation example provides a method for preparing pre-steady-state low-sodium nano-silicon-PCE mother liquor B, which includes the following steps: (1) Measure 63.5g of deionized water and 87.5g of ether polycarboxylate superplasticizer with a solid mass fraction of 40% and add them to a reactor equipped with a disperser. Stir at 300r / min for 10 minutes at 20°C.

[0040] (2) While maintaining a stirring speed of 300 r / min, 700 g of low sodium nano silica sol with a solid mass fraction of 25% was added dropwise into the reactor over 25 minutes. After the addition was completed, the speed of the disperser was increased to 2500 r / min and stirring was continued for 30 minutes.

[0041] (3) Dissolve 19g of calcium formate in 130g of pre-weighed deionized water to form a clear liquid. Then, drop the clear liquid into the reactor at a uniform rate within 10 minutes. After the drop is completed, adjust the speed of the disperser to 1000r / min and continue stirring for 15 minutes before discharging.

[0042] (4) After sampling and testing, the final solid mass fraction of the prepared mother liquor B was 22.9%, of which the solid mass ratio of nano-SiO2 to polycarboxylate superplasticizer was 5:1; after the mother liquor B was left to stand for 24 hours at 20℃-25℃, there was no visible gelation, layering and hard precipitation. Example 1

[0043] This embodiment provides a method for high-strength adhesive bonding maintenance of high-voltage insulators, including the following steps: (1) Accurately weigh 850g of P.O52.5R type ordinary Portland cement, 110g of S95 grade granulated blast furnace slag powder, 40g of ultrafine limestone powder with a median particle size D50 of 2-6μm and 1.5g of industrial grade calcium formate, put them into a dry powder mixer and mix for 3 minutes to form a uniform dry premixed powder; then add 1150g of quartz sand and continue to dry mix for 2 minutes.

[0044] (2) Measure 180g of deionized water as the main mixing water, add 35.0g of the mother liquor B obtained in Preparation Example 2 and 0.3g of nonionic organosilicon defoamer to it, stir and disperse evenly to obtain the main mixture.

[0045] (3) Add the obtained main mixture to the dry-mixed powder at once, and start the planetary cement mortar mixer for mixing; start timing the moment the main mixture comes into contact with the powder, and when the mixing reaches 90 seconds, inject the post-calcium source water prepared by dissolving 4.0g of industrial grade calcium formate in 32g of reserved deionized water into the mixing pot at once, continue mixing for 90 seconds and then stop mixing to obtain the insulator adhesive slurry.

[0046] (4) Inject the obtained slurry into the glued gap between the cleaned and assembled porcelain insulator and metal accessories, place it on the vibration table to vibrate and vent for 30 seconds, and smooth the surface.

[0047] (5) Move the grouting insulator into a programmable temperature and humidity curing box and let it stand for 90 minutes at 25°C and 95% relative humidity.

[0048] (6) After the static curing is completed, the temperature of the curing chamber is raised to 55°C at a rate of 6°C / h, and then kept at this temperature for 10 hours.

[0049] (7) After the constant temperature is completed, cut off the heating power supply and let the temperature inside the box cool down naturally to no more than 35°C. Remove the insulator from the curing box and complete the gluing operation. Example 2

[0050] This embodiment provides a method for high-strength adhesive bonding maintenance of high-voltage insulators, including the following steps: (1) Accurately weigh 880g of P.O52.5R type ordinary Portland cement, 90g of S95 grade granulated blast furnace slag powder, 30g of ultrafine limestone powder with a median particle size D50 of 2-6μm and 1.5g of industrial grade calcium formate, put them into a dry powder mixer and mix for 3 minutes to form a uniform dry premixed powder; then add 1000g of quartz sand and continue to dry mix for 2 minutes.

[0051] (2) Measure 173g of deionized water as the main mixing water, add 33.0g of the mother liquor B obtained in Preparation Example 1 and 0.5g of nonionic organosilicon defoamer to it, stir and disperse evenly to obtain the main mixture.

[0052] (3) Add the obtained main mixture to the dry-mixed powder at once, and start the planetary cement mortar mixer for mixing; start timing the moment the main mixture comes into contact with the powder, and when the mixing reaches 90 seconds, inject the post-calcium source water prepared by dissolving 3.7g of industrial grade calcium formate in 24g of reserved deionized water into the mixing pot at once, continue mixing for 90 seconds and then stop mixing to obtain the insulator adhesive slurry.

[0053] (4) Inject the obtained slurry into the glued gap between the porcelain part and the metal accessory of the insulator, place it on the vibration table to vibrate and vent for 30 seconds, and smooth the surface.

[0054] (5) Move the grouting insulator into a programmable temperature and humidity curing box and let it stand for 90 minutes at 22°C and 95% relative humidity.

[0055] (6) After the static curing is completed, the temperature of the curing chamber is raised to 53°C at a rate of 5°C / h, and then kept at this temperature for 12 hours.

[0056] (7) After the constant temperature is completed, cut off the heating power supply and let the temperature inside the box cool down naturally to no more than 35°C. Remove the insulator from the curing box and complete the gluing operation. Example 3

[0057] This embodiment provides a method for high-strength adhesive bonding maintenance of high-voltage insulators, including the following steps: (1) Accurately weigh 830g of P.O52.5R type ordinary Portland cement, 130g of S95 grade granulated blast furnace slag powder, 40g of ultrafine limestone powder with a median particle size D50 of 2-6μm and 2.0g of industrial grade calcium formate, put them into a dry powder mixer and mix for 3 minutes to form a uniform dry premixed powder; then add 1150g of quartz sand and continue to dry mix for 2 minutes.

[0058] (2) Measure 183g of deionized water as the main mixing water, add 39.0g of the mother liquor B obtained in Preparation Example 3 and 0.5g of nonionic organosilicon defoamer to it, stir and disperse evenly to obtain the main mixture.

[0059] (3) Add the obtained main mixture to the dry-mixed powder at once, and start the planetary cement mortar mixer for mixing; start timing the moment the main mixture comes into contact with the powder, and when the mixing reaches 90 seconds, inject the post-calcium source water prepared by dissolving 4.2g of industrial grade calcium formate in 45g of reserved deionized water into the mixing pot at once, continue mixing for 90 seconds and then stop mixing to obtain the insulator adhesive slurry.

[0060] (4) Inject the obtained slurry into the glued gap between the porcelain part and the metal accessory of the insulator, place it on the vibration table to vibrate and vent for 30 seconds, and smooth the surface.

[0061] (5) Move the grouting insulator into a programmable temperature and humidity curing box and let it stand for 90 minutes at 25°C and 95% relative humidity.

[0062] (6) After the static curing is completed, the temperature of the curing chamber is raised to 57°C at a rate of 8°C / h, and then kept at this temperature for 10 hours.

[0063] (7) After the constant temperature is completed, cut off the heating power supply and let the temperature inside the box cool down naturally to no more than 35°C. Remove the insulator from the curing box and complete the gluing operation. Example 4

[0064] This embodiment provides a method for high-strength adhesive bonding maintenance of high-voltage insulators, which includes the following steps: (1) Accurately weigh 850g of P.O52.5R type ordinary Portland cement, 110g of S95 grade granulated blast furnace slag powder, 40g of ultrafine limestone powder with a median particle size D50 of 2-6μm and 1.5g of industrial grade calcium formate, put them into a dry powder mixer and mix for 3 minutes to form a uniform dry premixed powder; then add 1150g of quartz sand and continue to dry mix for 2 minutes.

[0065] (2) Take 170g of deionized water as the main mixing water, add 35.0g of the mother liquor B obtained in Preparation Example 2 and 0.3g of nonionic organosilicon defoamer to it, stir and disperse evenly to obtain the main mixture.

[0066] (3) Add the obtained main mixture to the dry-mixed powder at once, and start the planetary cement mortar mixer for mixing; start timing the moment the main mixture comes into contact with the powder, and when the mixing reaches 90 seconds, inject the post-calcium source water prepared by dissolving 4.0g of industrial grade calcium formate in 42g of reserved deionized water into the mixing pot at once, continue mixing for 90 seconds and then stop mixing to obtain the insulator adhesive slurry.

[0067] (4) Inject the obtained slurry into the glued gap between the porcelain part and the metal accessory of the insulator, place it on the vibration table to vibrate and vent for 30 seconds, and smooth the surface.

[0068] (5) Move the grouting insulator into a programmable temperature and humidity curing box and let it stand for 90 minutes at 25°C and 95% relative humidity.

[0069] (6) After the static curing is completed, the temperature of the curing chamber is raised to 55°C at a rate of 6°C / h, and then kept at this temperature for 10 hours.

[0070] (7) After the constant temperature is completed, cut off the heating power supply and let the temperature inside the box cool down naturally to no more than 35°C. Remove the insulator from the curing box and complete the gluing operation.

[0071] Comparative Example 1: Compared to Example 1, the difference lies in the omission of the preparation and delayed injection steps of the post-calcium source water. The 4.0g of industrial-grade calcium formate used in Example 1 for preparing the post-calcium source water is directly added to the dry powder material and dry-mixed together. 32g of reserved deionized water is combined with 180g of main mixing water and added to the mixing pot at once as 212g of main mixing water. The main mixture is continuously stirred for 180 seconds after contacting the powder, and then stopped; no secondary liquid injection is performed during this process. All other raw material quantities and process conditions are the same as in Example 1.

[0072] Comparative Example 2: Compared to Example 1, the difference lies in that: instead of adding the mother liquor B obtained in Preparation Example 2, the effective components contained in 35.0g of mother liquor B are directly added to the main mixing water as independent raw materials. Specifically, 2.38g of ether-based polycarboxylate superplasticizer with a solid mass fraction of 50%, 17.85g of low-sodium nano-silica sol with a solid mass fraction of 30%, 0.455g of industrial-grade calcium formate, and 14.315g of deionized water are stirred and dispersed together with 180g of main mixing water to obtain the main mixture. The amounts of other raw materials and process conditions are the same as in Example 1.

[0073] Comparative Example 3: Compared to Example 1, the difference lies in the change of the constant temperature curing temperature. After grouting, the insulators were left to stand for 90 minutes at 25°C and 95% relative humidity. Then, the temperature of the curing box was increased to 85°C at a rate of 15°C / h, and maintained at 85°C for 10 hours. After the constant temperature curing period, the heating power was cut off, and the temperature inside the box was allowed to cool naturally to no higher than 35°C before the insulators were removed from the curing box. The remaining raw material quantities and process conditions were the same as in Example 1.

[0074] Comparative Example 4: Compared to Example 1, the difference lies in the use of a modified mother liquor B0 (containing no nano-SiO2) to replace mother liquor B in Example 1 by the same mass. The modified mother liquor B0 is prepared as follows: based on Preparation Example 2, low-sodium nano-silica sol is not added, and an equal mass of deionized water is used instead of low-sodium nano-silica sol. Other raw materials and preparation steps are the same as in Preparation Example 2. The 35.0g of mother liquor B in Example 1 is replaced with 35.0g of modified mother liquor B0, and the main mixing water is adjusted from 180g to 174.6g. The amounts of other raw materials and process conditions are the same as in Example 1.

[0075] Comparative Example 5: Compared to Example 1, the difference lies in that: granulated blast furnace slag powder and ultrafine limestone powder are not added to the cementitious base, and the 110g of granulated blast furnace slag powder and 40g of ultrafine limestone powder in Example 1 are all replaced by P.O52.5R type ordinary Portland cement by equal mass, that is, the amount of P.O52.5R type ordinary Portland cement is changed to 1000g. The remaining raw material amounts and process conditions are the same as in Example 1.

[0076] Comparative Example 6: Compared to Example 1, the difference lies in that: ultrafine limestone powder is not added to the cementitious base, and the 40g ultrafine limestone powder in Example 1 is replaced by P.O52.5R type ordinary Portland cement, that is, the amount of P.O52.5R type ordinary Portland cement is changed to 890g, while the amount of granulated blast furnace slag powder remains 110g. The remaining raw material amounts and process conditions are the same as in Example 1.

[0077] Comparative Example 7: Compared to Example 1, the difference lies in that: granulated blast furnace slag powder is not added to the cementitious base, and the 110g of granulated blast furnace slag powder in Example 1 is replaced by P.O52.5R type ordinary Portland cement, that is, the amount of P.O52.5R type ordinary Portland cement is changed to 960g, while the amount of ultrafine limestone powder remains 40g. The remaining raw material amounts and process conditions are the same as in Example 1.

[0078] Test Example 1: Test objective: To evaluate the effects of the pre-steady-state low-sodium nano-silicon composite mother liquor and the staged addition process of calcium formate on the initial fluidity, fluidity retention over time, bleeding rate, and macroscopic defects of freshly mixed slurry.

[0079] The experimental steps are as follows: (1) Freshly mixed slurries prepared according to the predetermined mixing ratio in Examples 1 to 4, Comparative Example 1 and Comparative Example 2 were extracted as test samples. In order to compare the state before and after the addition of post-calcium source water, during the preparation process of Example 1, a portion of the slurry was taken as an intermediate control sample after the first wet mixing was completed and before the post-calcium source water was added.

[0080] (2) The flowability of each group of slurries was tested in an indoor environment at 25℃ and relative humidity not less than 50%. After mixing, each group of slurries was immediately divided into 4 portions and sealed, corresponding to the test nodes of 0 minutes, 30 minutes, 60 minutes and 90 minutes respectively. At each time point, independent samples were used for the jump table test, and the flow diameter in two mutually perpendicular directions was measured and the arithmetic mean was taken as the flowability at the corresponding time point. The 90-minute flowability retention rate was calculated according to the following formula: 90-minute flowability retention rate = 90-minute flowability / initial flowability × 100%.

[0081] (3) Take each group of freshly mixed slurry and put it into a graduated glass measuring cylinder. After compaction, stopper the cylinder and let it stand for 2 hours. After standing, remove the free water that has separated from the surface and record the volume. The bleeding rate is calculated according to the following formula: Bleeding rate = Free water volume / Total mixing water volume in the sample calculated according to the mix proportion × 100%.

[0082] (4) Pour the remaining slurry of each group into a cubic mold with a side length of 100 mm, and demold after standing in the mold at room temperature for 24 hours. Use a cutting machine to cut the test block longitudinally along the center position, count the maximum diameter of the abnormal large pores visible to the naked eye in the 100 square centimeter observation area in the center of the cut surface, and record whether there are traces of water bleeding or aggregate sinking on the cut surface.

[0083] The experimental results are shown in Table 1: Table 1: Test data on the workability and macroscopic defects of freshly mixed slurry for each sample

[0084] Note: The intermediate state in Example 1 is a process sample taken before the addition of post-calcium source water. It is only used for flowability and bleeding rate testing and is not used for hardening section defect evaluation.

[0085] As shown in Table 1, the initial fluidity of the freshly mixed slurry in Examples 1 to 4 ranged from 240.2 mm to 245.6 mm, the fluidity retention rate after 90 minutes ranged from 91.38% to 93.28%, the bleeding rate ranged from 0.24% to 0.33%, the maximum abnormal pore diameter in the cross-section ranged from 1.05 mm to 1.38 mm, and no obvious segregation or bleeding traces were observed on the cross-section. These results indicate that the staged addition process of the pre-mixed mother liquor and calcium formate is beneficial for improving the fluidity retention capacity of the slurry and for reducing bleeding and macroscopic pore defects.

[0086] In Example 1, the intermediate slurry maintained a fluidity retention rate of 96.17% and a bleeding rate of 0.13% after 90 minutes without the addition of post-calcium source water. This result indicates that the slurry exhibits high fluidity retention over time before the addition of post-calcium source water, providing a process basis for the stability of the slurry after the subsequent addition of post-calcium source water.

[0087] Compared to Example 1, Comparative Example 1 changed the post-addition of calcium formate to a one-time addition in the initial stage. Its 90-minute fluidity retention rate decreased to 38.79%, the bleeding rate increased to 1.41%, the maximum abnormal pore diameter in the cross-section increased to 3.54 mm, and localized water lines appeared. These results indicate that the timing of calcium formate addition has a significant impact on the fluidity, bleeding rate, and macroscopic defects of the slurry after hardening.

[0088] Comparative Example 2 replaced the pre-mixed mother liquor process with an independent on-site blending of each effective component. Its initial flowability was 213.7 mm, the flowability retention rate after 90 minutes was 64.20%, the bleeding rate was 1.22%, the maximum abnormal pore diameter in the cross-section was 2.76 mm, and slight aggregate settling was observed. These results indicate that the pre-mixed mother liquor treatment step is beneficial for improving the initial dispersion state and flowability retention of the freshly mixed slurry, and for reducing macroscopic defects after hardening.

[0089] Test Example 2: Test objective: To evaluate the effects of ambient temperature, nano-silica, slag powder and ultrafine limestone powder on the early hydration exothermic behavior and setting process of the cementitious system through isothermal calorimetry and setting time tests, and to provide macroscopic experimental data for the early strength development of the composite cementitious system under low temperature and humid heat conditions of 55℃.

[0090] The experimental steps are as follows: (1) Cemented cement paste samples without quartz sand were prepared as test objects according to the cementitious base composition, admixture dosage, and water-cement ratio of Example 1 and Comparative Examples 4, 5, 6, and 7, respectively. The cemented cement paste sample corresponding to Example 1 was divided into two parts and tested at 25°C and 55°C, respectively; the cemented cement paste samples corresponding to Comparative Examples 4 to 7 were all tested at 55°C. The hydration heat release rate and cumulative heat release were calculated based on the mass of the cementitious base.

[0091] (2) The hydration heat release characteristics of each group of samples were determined using an isothermal calorimeter. 10g of well-stirred gelling paste was weighed and placed into a glass ampoule, sealed, and then placed in a constant temperature calorimeter channel pre-adjusted to 25℃ or 55℃. The instrument continuously collected hydration heat release rate data over 48 hours, and the cumulative heat release was obtained by integration calculation. The occurrence time and peak rate of the main heat release peak were extracted from the curve.

[0092] (3) The setting time test shall be performed in accordance with the instruments and judgment methods of GB / T1346. After each group of neat paste is put into the standard mold, it shall be placed in a constant temperature and humidity curing chamber set at 25℃ or 55℃ and relative humidity not less than 90% for static curing. During the test, the depth of penetration of the test needle shall be measured using a Vicat apparatus, and the initial setting time and final setting time of each sample shall be recorded.

[0093] The experimental results are shown in Table 2: Table 2: Results of hydration heat release parameters and setting time for each gelling system

[0094] As shown in Table 2, compared with the 25℃ condition, the time of occurrence of the main exothermic peak in Example 1 at 55℃ was advanced from 13.84 hours to 6.12 hours, the cumulative heat release over 24 hours increased from 135.4 J / g cementitious material to 243.6 J / g cementitious material, and the cumulative heat release over 48 hours increased from 182.7 J / g cementitious material to 285.9 J / g cementitious material. The initial setting time was shortened from 184 minutes to 96 minutes, and the final setting time was shortened from 246 minutes to 138 minutes. These results indicate that the 55℃ condition is beneficial for increasing the early hydration heat release rate of this cementitious system and advancing the setting process.

[0095] Compared with Example 1, after removing nano-silica in Comparative Example 4, the appearance time of the main exothermic peak at 55°C was delayed to 8.27 hours, the peak value of the exothermic peak decreased to 4.35 mW / g cementitious material, the cumulative heat release over 24 hours decreased to 212.8 J / g cementitious material, and the initial setting time and final setting time were extended to 114 minutes and 162 minutes, respectively. These results indicate that the addition of nano-silica is beneficial to improving the early hydration heat release level and setting rate of the composite cementitious system at 55°C.

[0096] In Comparative Example 5, after replacing slag powder and ultrafine limestone powder with ordinary Portland cement, the main exothermic peak appeared earlier at 5.43 hours, the peak value increased to 6.72 mW / g cementitious matrix, and the initial setting time and final setting time were shortened to 62 minutes and 93 minutes, respectively. Compared with Example 1, Comparative Example 5 showed more concentrated hydration exothermics and a shorter setting time. These results indicate that the combined incorporation of slag powder and ultrafine limestone powder is beneficial for regulating the early exothermic process and maintaining a suitable setting time window.

[0097] The test results of Comparative Examples 6 and 7 show that removing ultrafine limestone powder or slag powder alone alters the position of the exothermic peak, the cumulative heat release, and the setting time of the system. Specifically, the main exothermic peak in Comparative Example 6 occurred at 7.65 hours, while the cumulative heat release over 48 hours in Comparative Example 7 was 261.8 J / g of cementitious base. These results indicate that ultrafine limestone powder and slag powder have different effects on the early hydration heat release and the sustained heat release process within 48 hours of the system. Using both in combination is beneficial for balancing the setting process and the hydration heat release level within 48 hours.

[0098] Test Example 3: Test objective: To evaluate the influence of nano-silica on the early strength development of cementitious systems by measuring the flexural and compressive strength of standard-sized adhesive specimens at different ages, to investigate the influence of slag powder and ultrafine limestone powder on the mid-to-late-stage strength, and to compare the differences in mechanical properties of specimens under different humid heat curing temperature regimes.

[0099] The experimental steps are as follows: (1) Freshly mixed adhesive slurry corresponding to Examples 1 to 4 and Comparative Examples 3 to 7 were selected as test objects for mechanical properties. The dry powder material and liquid phase component were weighed according to the mixing ratio of each group, and mixed and stirred using a standard mortar mixer.

[0100] (2) The specimen size, molding method, flexural strength test method and compressive strength test method shall be performed in accordance with GB / T17671-2021; the specimen mix ratio, water-cement ratio, admixture dosage and curing system shall be performed in accordance with the process scheme corresponding to each embodiment or comparative example. The stirred slurry shall be divided into two layers and placed into a triple metal mold of 40mm×40mm×160mm. The mold shall be vibrated and molded on a vibrating table, the surface of the mold shall be smoothed and the group shall be marked.

[0101] (3) After each group of specimens was molded, it was first placed in an environment of 20℃-30℃ and relative humidity not less than 85% and left to stand for 90 minutes. Subsequently, Examples 1 to 4 and Comparative Examples 4 to 7 were treated according to the low temperature and humid heat curing system of 55℃, and Comparative Example 3 was treated according to the high temperature and humid heat curing system of 85℃.

[0102] (4) All test ages were calculated from the first contact time between the slurry and the powder. Independently molded specimens were used for each test age. Specimens were demolded immediately after reaching 18 and 24 hours of age and subjected to early mechanical testing. Specimens used for 7-day and 28-day tests were demolded after 24 hours and then transferred to a standard constant temperature and humidity curing environment at 20℃ for continued curing until 7 and 28 days of age. Upon reaching the predetermined ages, the flexural and compressive strengths of each group of specimens were measured using a computer-controlled flexural and compressive strength testing machine, and the corresponding failure loads were recorded.

[0103] The experimental results are shown in Table 3:

[0104] Table 3: Test results of flexural strength and compressive strength of standard-sized adhesive specimens at different ages in each group

[0105] As shown in Table 3, under low-temperature and humid heat curing conditions of 55℃, Examples 1 to 4 exhibited compressive strengths ranging from 37.1 MPa to 39.4 MPa after 18 hours, 45.8 MPa to 48.1 MPa after 24 hours, and 82.9 MPa to 85.2 MPa after 28 days. These results indicate that Examples 1 to 4 can achieve high early strength at relatively low humid heat curing temperatures and maintain strength growth over subsequent curing periods.

[0106] Compared with Example 1, Comparative Example 3, after high-temperature and humid heat curing at 85℃, exhibited compressive strengths of 52.3 MPa at 18 hours and 55.7 MPa at 24 hours, which were higher than those of Example 1 at the corresponding ages. However, its 7-day and 28-day compressive strengths were 61.4 MPa and 64.8 MPa, respectively, lower than those of Example 1 (68.2 MPa and 84.5 MPa). These results indicate that higher-temperature and humid heat curing is beneficial for improving early strength but detrimental to the later strength growth of the system; low-temperature and humid heat curing at 55℃ is beneficial for balancing early strength and 28-day strength.

[0107] In Comparative Example 4, after removing nano-silica, the compressive strength at 18 hours was 21.4 MPa and at 24 hours was 29.8 MPa, both lower than that of Example 1. This result indicates that the addition of nano-silica is beneficial for improving the early compressive strength of this system.

[0108] In Comparative Example 5, after replacing all the slag powder and ultrafine limestone powder with ordinary Portland cement, the 28-day compressive strength was 73.5 MPa, lower than the 84.5 MPa of Example 1. This result indicates that the combined incorporation of slag powder and ultrafine limestone powder is beneficial for improving the later-stage strength of this system.

[0109] Further comparison of Comparative Examples 6 and 7 shows that, after removing the ultrafine limestone powder alone, the 18-hour compressive strength of Comparative Example 6 is 33.2 MPa; while after removing the slag powder alone, the 28-day compressive strength of Comparative Example 7 is 74.9 MPa. These results indicate that ultrafine limestone powder has a certain influence on early-stage strength, and slag powder has a certain influence on later-stage strength. The combined use of both is beneficial for this adhesive system to balance both early-stage and later-stage strength under low-temperature and humid curing conditions at 55℃.

[0110] Test Example 4: Test objectives: To evaluate the load retention capacity and appearance integrity of adhesives under alternating temperature conditions through thermal cycling tests and mechanical destructive load tests; and to evaluate the effects of different humid heat curing temperature regimes on the water absorption characteristics and volume stability of hardened adhesives through boiling water absorption rate, linear drying shrinkage rate, and autoclaving expansion rate tests.

[0111] The experimental steps are as follows: (1) Preparation of high-voltage insulator solid specimens for mechanical testing and standard-sized adhesive specimens for physical performance testing. The high-voltage insulator solid specimens were prepared using the material ratios and process parameters corresponding to Examples 1, 4 and Comparative Example 3. Specifically, insulator porcelain parts and metal accessories of the same type and specification were selected, and the corresponding freshly mixed adhesive slurry was injected into the adhesive gaps between the cleaned and assembled insulator porcelain parts and metal accessories. After vibration degassing and surface smoothing, the specimens were cured according to the static curing and temperature regime of the corresponding examples or comparative examples for subsequent thermal cycling and mechanical destructive load testing.

[0112] Standard-sized adhesive specimens were prepared using freshly mixed adhesive slurry from the same batch as the corresponding physical specimens. Specifically, the slurry was filled into a 40mm×40mm×160mm triple metal mold, compacted and smoothed, and then cured under the same static curing and temperature regime as the corresponding physical specimens. These specimens were then used for subsequent tests of boiling water absorption, linear drying shrinkage, and autoclaving expansion.

[0113] (2) Six parallel samples were prepared for each group of solid glued insulators. Three of them were directly subjected to mechanical failure load test without thermal cycling, and the arithmetic mean of the results was taken as the initial failure load; the other three were subjected to thermal cycling and then mechanical failure load test, and the arithmetic mean of the results was taken as the failure load after cycling. The load retention rate was calculated according to the following formula: Load retention rate = Average failure load after cycling / Average initial failure load × 100%.

[0114] (3) The thermal cycling test process is as follows: The solid glued insulator is placed in a high and low temperature alternating test chamber, cooled from room temperature to -40℃ and held for 2 hours, then heated to 85℃ and held for 2 hours, which constitutes one thermal cycling cycle. A total of 20 cycles are performed. The specimens in each test group are heated and cooled at the same rate. After the cycle is completed, check and record whether there are visible cracks, peeling, spalling or interface openings in the glued parts; then, the mechanical failure load is measured on a horizontal tensile testing machine using the same fixture, loading direction and loading rate.

[0115] (4) The physical properties and volume stability of the hardened adhesive were tested on standard-sized adhesive specimens prepared in the same batch. The boiling water absorption rate was calculated by comparing the mass of the specimen after drying to constant weight with the mass after boiling and water absorption saturation. The linear drying shrinkage rate was calculated by measuring the length change of the standard specimen under specified constant temperature and humidity conditions. The autoclaving expansion rate was calculated by measuring the length change of the specimen before and after autoclaving treatment.

[0116] The experimental results are shown in Table 4: Table 4: Test results of load retention rate at failure of solid glued parts and volume stability of standard-sized adhesive specimens for each group

[0117] As shown in Table 4, after 20 cycles of thermal cycling, the solid glued parts of Examples 1 and 4 had destructive loads of 256.8 kN and 249.5 kN, respectively, with load retention rates of 97.16% and 96.44%. No visible cracks, peeling, or interface openings were observed in the glued areas after cycling. These results indicate that solid glued parts prepared using a 55°C low-temperature damp heat curing regime exhibit high mechanical load retention and good appearance integrity under the aforementioned thermal cycling conditions.

[0118] Compared to Example 1, Comparative Example 3 underwent high-temperature and humid heat curing at 85°C. Its initial destructive load was 251.2 kN, and the destructive load after cycling was 185.4 kN, with a load retention rate of 73.81%. Furthermore, visible fine cracks and localized peeling appeared on the surface of the gelled layer. These results indicate that the adhesive parts prepared under higher-temperature and humid heat curing conditions have lower load retention capacity after thermal cycling than the Example group.

[0119] The physical property test results of standard-sized adhesive specimens from the same batch showed that the boiling water absorption rates of Examples 1 and 4 were 3.42% and 3.65%, respectively; the linear drying shrinkage rates were 0.038% and 0.041%, respectively; and the autoclaving expansion rates were 0.065% and 0.069%, respectively. The boiling water absorption rate, linear drying shrinkage rate, and autoclaving expansion rate of Comparative Example 3 were 5.87%, 0.076%, and 0.114%, respectively. These results indicate that a low-temperature, humid heat curing regime at 55℃ is beneficial for reducing the water absorption rate and volumetric deformation rate of the hardened adhesive, and provides macroscopic performance support for maintaining mechanical load on solid adhesive parts under alternating hot and cold conditions.

[0120] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for high-strength adhesive bonding maintenance of high-voltage insulators, characterized in that, Includes the following steps: (1) The cementitious base containing silicate cement, slag powder and ultrafine limestone powder is mixed with the first part of calcium formate to form a uniform dry premixed powder; then quartz sand is added and dry mixing is continued; (2) Measure out deionized water as the main mixing water, add pre-stabilized low-sodium nano-silicon-PCE mother liquor B and defoamer to it, stir and disperse evenly to obtain the main mixture; (3) Add the main mixture to the powder obtained in step (1) for wet mixing; After the main mixture comes into contact with the powder and is stirred for a first preset time, the post-calcium source water, which is prepared by dissolving the second part of calcium formate in the reserved deionized water, is injected into the material being stirred, and stirring is continued for a second preset time to obtain the insulator adhesive slurry. (4) Inject the insulator adhesive slurry into the adhesive gap between the insulator porcelain and the metal accessories, vibrate to remove air and smooth the surface; (5) Move the grouting insulators into the curing box and let them stand for 90 minutes at a temperature of 22℃~25℃ and a relative humidity of not less than 95%. (6) After the static curing is completed, the temperature of the curing chamber is raised to 53℃~57℃ at a heating rate of 5℃ / h~8℃ / h, and the chamber is kept at a constant temperature of 53℃~57℃ for 10 hours~12 hours. (7) After the constant temperature is completed, allow the temperature inside the curing box to cool down naturally to no higher than 35°C, and then remove the insulator from the curing box.

2. The high-strength adhesive bonding maintenance method for high-voltage insulators according to claim 1, characterized in that, Based on the total mass of the cementitious base material as 100%, the cementitious base material is composed of 83% to 88% silicate cement, 9% to 13% slag powder and 3% to 4% ultrafine limestone powder by mass percentage.

3. The high-strength adhesive bonding maintenance method for high-voltage insulators according to claim 2, characterized in that, Based on the total mass of the cementitious base material, the addition amounts of other components are as follows: the pre-stabilized low-sodium nano-silica-PCE mother liquor B is 3.3% to 3.9%, the first part calcium formate is 0.15% to 0.20%, the second part calcium formate is 0.37% to 0.42%, the defoamer is 0.03% to 0.05%, and the mass ratio of the quartz sand to the cementitious base material is 1.0:1 to 1.15:

1.

4. The high-strength adhesive bonding maintenance method for high-voltage insulators according to claim 3, characterized in that, The total water-to-binder ratio of the insulator adhesive slurry is 0.22 to 0.26; the total water volume in the calculation of the total water-to-binder ratio includes the mass of the main mixing water, the mass of water contained in the pre-stabilized low-sodium nano-silicon-PCE mother liquor B, and the mass of the reserved deionized water; the mass of the reserved deionized water accounts for 12% to 20% of the total mass of the main mixing water and the reserved deionized water.

5. The high-strength adhesive bonding maintenance method for high-voltage insulators according to claim 1, characterized in that, The silicate cement is P.O52.5R type ordinary silicate cement; the slag powder is S95 grade granulated blast furnace slag powder; the median particle size D50 of the ultrafine limestone powder is 2μm to 6μm; the first part of calcium formate and the second part of calcium formate are both industrial grade calcium formate; the defoamer is a nonionic organosilicon defoamer.

6. The high-strength adhesive bonding maintenance method for high-voltage insulators according to claim 1, characterized in that, The final solid mass fraction of the pre-stabilized low-sodium nano-silicon-PCE mother liquor B is 18.1% to 22.9%, and the solid mass ratio of nano-SiO2 to polycarboxylate superplasticizer in the pre-stabilized low-sodium nano-silicon-PCE mother liquor B is 4:1 to 5:

1.

7. The high-strength adhesive bonding maintenance method for high-voltage insulators according to claim 1, characterized in that, The preparation method of the pre-steady low-sodium nano-silicon-PCE mother liquor B includes the following steps: S1. Add deionized water and ether polycarboxylate superplasticizer with a solid mass fraction of 40% to 50% to the reactor, and stir at a speed of 300 r / min to 500 r / min for 5 to 10 minutes at a temperature of 20℃ to 25℃. S2. While maintaining stirring, add low-sodium nano-silica sol with a solid mass fraction of 20% to 30% dropwise to the reaction vessel at a uniform rate over 15 to 25 minutes; after the addition is complete, increase the rotation speed to 1800 r / min to 2500 r / min and continue stirring for 20 to 30 minutes. S3. Dissolve calcium formate in pre-weighed deionized water to form a clear solution, and then drip the clear solution into the reaction vessel at a uniform rate over 5 to 10 minutes. After the dripping is complete, adjust the speed to 1000 r / min to 1500 r / min, continue stirring for 15 to 20 minutes, and then discharge the material.

8. The high-strength adhesive bonding maintenance method for high-voltage insulators according to claim 7, characterized in that, The raw materials used to prepare the pre-stabilized low-sodium nano-silicon-PCE mother liquor B are as follows (in parts by weight): Deionized water used for the bottom water of the reactor: 63.5 parts to 319 parts; Ether-based polycarboxylate superplasticizers with a solid mass fraction of 40%–50% at the factory: 68 parts–87.5 parts; Low-sodium nano-silica sol with a solid mass fraction of 20%–30%: 510–700 parts; Calcium formate: 11 to 19 parts; Deionized water used to dissolve calcium formate: 75 to 130 parts.

9. The high-strength adhesive bonding maintenance method for high-voltage insulators according to claim 1, characterized in that, In step (3), the wet mixing is carried out using a planetary cement mortar mixer; the timing starts the instant the main mixture comes into contact with the powder, the first preset time is 90 seconds; the second preset time is 90 seconds.

10. The high-strength adhesive bonding maintenance method for high-voltage insulators according to claim 1, characterized in that, In step (4), the vibration exhaust time is 30 seconds; in step (5), the curing box is a programmable temperature and humidity curing box; in step (7), the temperature inside the curing box is naturally cooled down by cutting off the heating power supply.